2018
DOI: 10.1111/eff.12405
|View full text |Cite
|
Sign up to set email alerts
|

Roles of discharge and temperature in recruitment of a cold‐water fish, the European grayling Thymallus thymallus, near its southern range limit

Abstract: Recruitment of salmonids is a result of density‐dependent factors, specifically egg production in the previous year, and density‐independent environmental processes driven by discharge and temperature. With the plethora of knowledge on major drivers of Atlantic salmon Salmo salar and brown trout Salmo trutta recruitment, there is a requirement to explore less known species, such as European grayling Thymallus thymallus, whose postemergence time coincides with period of increasing temperature and low discharge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…However, recruitment of grayling and trout was positively associated in an English chalk stream (Bašić, Britton, Cove, Ibbotson, & Gregory, 2018). Also, Alpine bullhead (Cottus poecilopus, Cottidae) is a strong competitor to juvenile brown trout where these species cooccur (Hesthagen & Heggenes, 2003;Holmen, Olsen, & Vøllestad, 2003).…”
Section: Interspecific Competitionmentioning
confidence: 99%
“…However, recruitment of grayling and trout was positively associated in an English chalk stream (Bašić, Britton, Cove, Ibbotson, & Gregory, 2018). Also, Alpine bullhead (Cottus poecilopus, Cottidae) is a strong competitor to juvenile brown trout where these species cooccur (Hesthagen & Heggenes, 2003;Holmen, Olsen, & Vøllestad, 2003).…”
Section: Interspecific Competitionmentioning
confidence: 99%
“…The chalk streams of southern England, such as the Hampshire Avon or Dorset Frome, are renowned to have more stable flow and temperature regimes than more rain-fed rivers and are likely to behave quite differently (Basic et al, 2018;Solomon & Paterson, 1980). By opting to treat our sample rivers as random representatives of Wales, we precluded making river-specific inferences because our river-specific estimates will have reduced variance due to shrinkage (Harrison et al, 2018).…”
Section: Generalisation Across and Beyond Walesmentioning
confidence: 99%
“…They suggested that methods with strong assumptions about the form of density-dependence in recruitment, such as the Beverton-Holt model, were appropriate for single data-rich stocks (e.g. Baglinière, Marchand, & Vauclin, 2005;Basic, Britton, Cove, Ibbotson, & Gregory, 2018), but that more data-driven, statistical models were emergence conditions, which could be more common under future climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment from eggs to age 0 juveniles was estimated as a density-dependent function modified by explanatory variables, as there is evidence for a negative effect of conspecific densities on annual grayling recruitment in the River Wylye (Bašić et al, 2018).…”
Section: Ecological Process Equationsmentioning
confidence: 99%